DNA methylation and genome defense in Neurospora crassa - Selker, Eric (Henry Stewart Talks, 2007)
Control of DNA methylation, repeat-induced point (RIP) mutation, relationship of chromatin modifications and DNA methylation, mutants that eliminate DNA methylation, roles of histone H3 methyltransferase (DIM-5) and heterochromatin protein 1 (HP1) in DNA methylation, indications of involvement of protein acetylation, methylation and phosphorylation in mechanism of DNA methylation, propagation of DNA methylation and the associated silenced chromatin state
Archived at 2021/02/25